1996
DOI: 10.3168/jds.s0022-0302(96)76487-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Antihypertensive Peptide from Casein Hydrolysate Produced by a Proteinase from Lactobacillus helveticus CP790

Abstract: Casein hydrolysate, produced by an extracellular proteinase from Lactobacillus helveticus CP790, was fractionated by two-step reverse-phase HPLC. Only one fraction showed antihypertensive activity as measured by systolic blood pressure in spontaneously hypertensive rats after oral administration. Ten peptides in the fraction were further purified and identified by analysis of amino acid sequences. Each identified peptide was chemically synthesized, and the antihypertensive activity of each peptide was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
199
0
7

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 353 publications
(218 citation statements)
references
References 14 publications
5
199
0
7
Order By: Relevance
“…The strains L. helveticus CP790 [57,137] and L. helveticus LBK-16 [110] have been successfully applied for the formation of VPP and IPP in two commercial fermented-milk products with antihypertensive capacity (Ameal S TM and Evolus ® ). Similarly, other L. helveticus strains such as NCC 2765 [100], PR4 [69] or 130B4 from camel milk [113] and in a further study [82] two highly proteolytic strains of L. helveticus (MI 1198, MI 1263), as well as strains of Lc.…”
Section: Starter Culturesmentioning
confidence: 99%
“…The strains L. helveticus CP790 [57,137] and L. helveticus LBK-16 [110] have been successfully applied for the formation of VPP and IPP in two commercial fermented-milk products with antihypertensive capacity (Ameal S TM and Evolus ® ). Similarly, other L. helveticus strains such as NCC 2765 [100], PR4 [69] or 130B4 from camel milk [113] and in a further study [82] two highly proteolytic strains of L. helveticus (MI 1198, MI 1263), as well as strains of Lc.…”
Section: Starter Culturesmentioning
confidence: 99%
“…For instance, YKVPQL identified in a casein hydrolyzate and released by a proteinase from L. helveticus CP790, had a high in vivo ACE-inhibitory activity (IC50 22 M) but did not show any antihypertensive one [282] -probably as a consequence of degradation during the digestion process [137]. When the hydrolyzate was purified, another peptide sequence (KVLPVPQ) was found.…”
Section: Bioavailabilitymentioning
confidence: 99%
“…However, some peptides with in vivo antihypertensive activity -as is the sequence KVLPVPQ, and which did not show in vitro ACE-inhibitory activity, could be transformed to active forms via gastrointestinal digestion [282]. Simulation of digestion is also useful in studies of the mechanism of action of antihypertensive peptides with demonstrated in vivo activity.…”
Section: Bioavailabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, pancreatic digestion is needed to produce active peptide. For instance, the active form of peptide Lys-Val-Leu-Pro-Val-Pro-Glu is generated by hydrolysis of the glutamine residue at the C-terminal during pancreatic digestion [107]. The results are not completely predictive of the resistance of the bioactive peptides because they do not mimic all the physiological factors affecting food digestion, as pH variations, the relative amounts of the enzymes, the interactions with other molecules, and the ratio peptidase/tested compound.…”
Section: Bioavailabilitymentioning
confidence: 99%